(untitled) (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
One of the phenomena currently occurring is the rise of Korean food culture among Indonesian people. Indonesian people who like watching K-Dramas and following K-Pop trends are often interested in trying foods that often appear in dramas or uploaded by K-Pop idols. This research aims to assess the extent to which food quality, sub-culture and situational factors influence consumer preferences in terms of changing behavior and purchasing decisions. The research methodology used in this research is a quantitative method with quantitative data originating from primary and secondary data sources with statistical analysis using an inferential approach to produce clear and accurate research. The research findings indicate that food quality and situational factors individually do not significantly influence Indonesian purchasing decisions, with significance values of 0.125 and 0.116 respectively. Conversely, subculture significantly impacts purchasing decisions with a significance value of 0.000. In the simultaneous test, food quality, subculture, and situational factors collectively significantly influence purchasing decisions, as demonstrated by an F value of 21.116 with a significance value of 0.000 in the ANOVA test. Additionally, the coefficient of determination reveals that 53.1% of the variation in purchasing decisions is explained by food quality, subculture, and situational factors, leaving the remainder to be explained by other unstudied factors. Keywords: Globalization, Factors, Consumer Behavior.